Design and Simulation of a 6-Bit Successive-Approximation ADC Using Modeled Organic Thin-Film Transistors. (15th March 2016) - Pham, Huyen Thanh; Nguyen, Thang Vu; Pham-Nguyen, Loan; Sakai, Heisuke; Dao, Toan Thanh
Abstract : We have demonstrated a method for using proper models of pentacene P-channel and fullerene N-channel thin-film transistors (TFTs) in order to design and simulate organic integrated circuits. Initially, the transistors were fabricated, and we measured their main physical and electrical parameters. Then, these organic TFTs (OTFTs) were modeled with support of an organic process design kit (OPDK) added in Cadence. The key specifications of the modeled elements were extracted from measured data, whereas the fitting ones were elected to replicate experimental curves. The simulating process proves that frequency responses of the TFTs cover all biosignal frequency ranges; hence, it is reasonable to deploy the elements to design integrated circuits used in biomedical applications. Complying with complementary rules, the organic circuits work properly, including logic gates, flip-flops, comparators, and analog-to-digital converters (ADCs) as well. The proposed successive-approximation-register (SAR) ADC consumes a power of 883.7  µ W and achieves an ENOB of 5.05 bits, a SNR of 32.17 dB at a supply voltage of 10 V, and a sampling frequency of about 2 KHz.